2015
DOI: 10.5551/jat.26658
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Circulating Microparticles in Patients with Chronic Cardiorenal Disease

Abstract: Aim: Cardiac and renal diseases are common disorders that frequently coexist. We tested the hypothesis that the levels of circulating endothelial-derived apoptotic microparticles (EDA-MPs; CD31 CD42b AN V ) and platelet-derived apoptotic microparticles (PDA-MPs; CD31 CD42b AN V ) are useful biomarkers for predicting the presence of cardiorenal disease (CRD). Methods: A total of 68 patients with chronic kidney disease (CKD) and angina pectoris (CKD-AP) undergoing cardiac catheterization were prospectively enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
0
18
1
2
Order By: Relevance
“…Renal insufficiency is considered to be an independent risk factor for CAD 16) ; furthermore, CAD patients with renal insufficiency have worse clinical outcomes compared with patients without renal insufficiency 79) . Coronary revascularization has been demonstrated to be effective in improving prognosis in CAD patients with renal insufficiency 18, 19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal insufficiency is considered to be an independent risk factor for CAD 16) ; furthermore, CAD patients with renal insufficiency have worse clinical outcomes compared with patients without renal insufficiency 79) . Coronary revascularization has been demonstrated to be effective in improving prognosis in CAD patients with renal insufficiency 18, 19) .…”
Section: Discussionmentioning
confidence: 99%
“…Renal insufficiency is an independent risk factor for coronary artery disease (CAD) 16) . Furthermore, previous studies reported that CAD patients with renal insufficiency had worse clinical outcomes compared with those without renal insufficiency 79) .…”
Section: Introductionmentioning
confidence: 99%
“…Stenting in stable coronary atherosclerotic lesions is associated with a substantial release of pMVs (Horn et al, 2015). Interestingly, the link with increased circulating pMV levels is more consistent with coronary artery disease patients than in those with chronic kidney disease (Chen et al, 2014). Indeed, overproduction of pMVs and platelet activation with suppressed aggregation may be even implicated in the pathogenesis of coagulation abnormalities in children with congenital heart disease (Horigome et al, 2002; Ismail and Youssef, 2012).…”
Section: Platelet-derived Microvesicles and Cardiovascular Diseasementioning
confidence: 99%
“…Circulating MPs have been the most studied EVs in humans with CKD and ESRD, conditions in which MPs have been associated with endothelial dysfunction, 67 cardiovascular mortality, 68,69 increased risk for calcification, 70,71 anemia, 72,73 and disease-specific alteration in coagulation. 74 In a study of a heterogeneous group of patients with chronic renal failure and those on peritoneal dialysis and hemodialysis, all patients compared with healthy controls had higher levels of endothelial-derived microparticles (EMPs) and MPs of leukocyte origin.…”
Section: Ckd/uremia/esrdmentioning
confidence: 99%